Profitability, Firm Size, and Tax Avoidance: A Review of the Indonesian Energy Sector (2020-2024) - Angelia Setiadi; Retno Indah Hernawati; Chia-Ming Sun (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This study aims to examine how profits and company size affect tax avoidance in energy companies listed on the stock exchange between 2022 and 2024. This study applies a quantitative approach using secondary data from annual financial reports. The population data was taken from 18 energy companies listed on the Indonesia Stock Exchange, while the sample selection was conducted using purposive sampling. The main phenomenon affecting the test results is the existence of incentives for highly profitable companies to engage in tax avoidance due to the potential for more significant tax savings. In addition, large companies usually have more resources and complex organizational structures, which give them more opportunities to carry out innovative and aggressive tax planning. It is hoped that this study can offer a fresh understanding of tax avoidance practices in the energy sector in Indonesia. The impact of this study is important for authorities to understand the relationship between corporate profitability, entity size, and tax avoidance practices, especially in the energy sector, which plays a strategic role. This understanding can assist in formulating more appropriate taxation policies to maintain economic stability and fiscal justice. The novelty of this research lies in its focus on business entities in the energy sector listed on the Stock Exchange from 2022 to 2024, which is a dynamic period marked by global commodity price fluctuations, changes in energy policy, and significant geopolitical challenges.